Editorial - Crystal Fulton (Information Research: An International Electronic Journal)
Welcome to 2025 and a new year in Information Research. 2025 marks the 30th anniversary of Information Research, a major milestone in the life of an academic journal founded to provide a forum for research in Information Science (please watch our website for our call for submissions to a 30th anniversary special issue!). Notably, the journal still follows an open access publication model as it did from its inception at a time when ideas around open science tended not to be at the heart of research and publishing.